Carbon Dioxide versus Saline Tissue Expanders: Does It Matter?. Issue 1 (January 2016) - Ascherman, Jeffrey A.; Zeidler, Kamakshi R.; Jacoby, Adam; Appel, James Z.; Berkowitz, R. Laurence; Castle, John; Colwell, Amy; Chun, Yoon S.; Johnson, Debra J.; Mohebali, Khashayar
Abstract : Background: Implant-based breast reconstruction is the most common reconstructive technique in the United States. Despite its popularity, saline-based tissue expansion still has its limitations, including lengthy expansion times, large uncomfortable bolus dosing, and frequent percutaneous injections/expansion visits. Ideally, a novel technology would eliminate frequent, percutaneous saline injections and allow patients to perform expansion at home, reducing the disruptive experience of current tissue expansion. Methods: Within the past 6 years, the AeroForm tissue expander system has used remotely activated carbon dioxide release as the fill medium instead of saline, eliminating many limitations of traditional tissue expanders. In this article, the authors first review the relevant literature concerning carbon dioxide–based tissue expansion in animal and human models. The authors then analyze the similarities and differences between two groundbreaking human trials (i.e., Patient Activated Controlled Expansion and AirXpanders Patient Activated Controlled Tissue Expander) with carbon dioxide–based expanders and discuss the risks and benefits associated with this new technology. Results: At their site, the authors have enrolled 34 patients using 36 experimental devices in total, and have found significantly shorter expansion and overall reconstruction times in the patient-controlled tissue expander group. Conclusions: The authors believe that carbon dioxide–based devices may play a significant role in the future of implant-based breast reconstruction, and may be widely applicable to other areas of plastic surgery that also involve tissue expansion.